Effect of metal content from sewage sludge on the growth of Orthosiphon stamineus - Zaidi, Nur Syamimi; Sohaili, Johan; Loh, Zhang Zhan; Arisa, Azmi; Hussein, Norelyza (Environmental and Toxicology Management, 2021)
Municipal sewage sludge can be used as fertilizer as it contains a lot of nutrients. By focusing on copper (Cu), iron (Fe), manganese (Mn), and zinc (Zn) contents in municipal sewage sludge from primary oxidation ponds and in plant tissue sections, this study attempts to explain the relationship between plant yield and metal concentrations. Raw sludge samples were collected, air-dried, and ground to powder form at the beginning of fieldwork. The metal concentrations of sewage sludge were copper 6.9 mg/kg; iron 330.2 mg/kg manganese 6.7 mg/kg and zinc 9.1 mg/kg. Orthosiphon stamineus (cat’s whiskers) was selected and the plant received a different quantity of sludge application ranging from 1 g to 4 g per plant weekly for six consecutive weeks while observations were done for eleven weeks. Physical parameters such as shrub width and height were monitored to determine plant growth. Through this study, the determined optimum sewage sludge dosage for cats’ whiskers was between 2 to 3 g per plant.